KUALITAS PEMAIN BULUTANGKIS U15 PUTRA PBSI WONOSOBO TAHUN 2017 - man, Surat (Universitas Negeri Semarang, 2017)
This research background of badminton player U15 son PBSI Wonosobo who have often follow the national tournament but not the achievement that allegedly have quality problems. This study aims to find the quality of engineering, physical and mental players bulutangkkis U15 men PBSI Wonosobo 2017 which is a quantitative study with normative descriptive approach. The results showed; 1). The technical qualities of badminton players U15 putus PBSI Wonosobo are; service long enough quality, good quality lop, excellent quality smash, sufficient quality drop shot.2). Its physical properties; vertical jump quality is sufficient, court agility excellent quality, skipping roap good quality, set up of enough quality, push ups of sufficient quality, beep test gets good quality. 3). Its mental quality is; tranquility of good quality attitude, sufficient qualified anxiety, sufficient quality panic. To players badminton U15 men PBSI Wonosobo 2017, should add technical training on long service, and hot drops. To physically focus on leg power exercises, set up, push ups. As for mental please increase exercise to overcome anxiety and panic. All that for the quality of the game to be increased.